Power-velocity relationship and muscular strength in female volleyball players during preparatory period and competition season - Busko, K. (Acta of Bioengineering and Biomechanics, 2019)
Purpose: The aim of the study was to investigate changes of power-velocity relationship and muscular strength of female volleyball players during preparatory period and competition season. Methods: The study was conducted on eleven female volleyball players: age 21.6±1.7 years, body height 177.9±4.7 cm, body mass 71.3±6.6 kg. Power-velocity relationship was determined by means of five maximal 10-second cycloergometer efforts with external loads equal to: 2.5, 5, 7.5, 10 and 12.5% of body weight (BW). The joint torque of flexors and extensors of an elbow, shoulder, hip, knee and trunk was measured using a torque meter. The measurement were taken before (I) and after (II) the preparatory period, after the first (III) and second (IV) competitive season. Results: The power with a load equal to 2.5, 5.0, 7.5, 10.0% BW increased significantly after first and second competitive season. The sums of joint torque for the lower and upper limb changed insignificantly. In the case of the right upper limb, sum of the joint torques was significantly reduced by 9.5% between measurement I and IV. Sum of the left upper limb was significantly decreased by 9.8% between measurement I and II. Sum of the joint torque of the trunk was significantly increased between measurements I and II, III and IV by 12.9%, 12.3% and 11.2%, respectively. Conclusion: Obtained results may suggest that selection of the training loads was adequate for training power output and muscle strength of lower limbs but too little emphasis was placed on development of strength in the muscles of the upper limbs.